2012
DOI: 10.1038/nature11692
|View full text |Cite
|
Sign up to set email alerts
|

An alternative route to cyclic terpenes by reductive cyclization in iridoid biosynthesis

Abstract: The iridoids comprise a large family of distinctive bicyclic monoterpenes that possess a wide range of pharmacological activities, including anticancer, anti-inflammatory, antifungal and antibacterial activities. Additionally, certain iridoids are used as sex pheromones in agriculturally important species of aphids, a fact that has underpinned innovative and integrated pest management strategies. To harness the biotechnological potential of this natural product class, the enzymes involved in the biosynthetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
303
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(327 citation statements)
references
References 33 publications
17
303
0
6
Order By: Relevance
“…The iridoid synthase is a member of the Rossmann-fold NAD(P) + -binding protein superfamily. It cyclizes 8-oxogeranial to cis-trans-iridodials and cis-trans-nepetalactol under the consumption of NAD(P)H [32]. In a proteomic analysis, however, no protein similar to the iridoid synthase from C. roseus could be detected in the secretions of iridoid-producing Chrysomelina larvae.…”
Section: Iridoid De Novo Synthesis: Late Stepsmentioning
confidence: 97%
See 1 more Smart Citation
“…The iridoid synthase is a member of the Rossmann-fold NAD(P) + -binding protein superfamily. It cyclizes 8-oxogeranial to cis-trans-iridodials and cis-trans-nepetalactol under the consumption of NAD(P)H [32]. In a proteomic analysis, however, no protein similar to the iridoid synthase from C. roseus could be detected in the secretions of iridoid-producing Chrysomelina larvae.…”
Section: Iridoid De Novo Synthesis: Late Stepsmentioning
confidence: 97%
“…The iridoid pathway starts with its key intermediate, geraniol diphosphate, and comprises a number of oxidation, reduction, glycosylation, and methylation reactions [5,29]. The biosynthesis of secologanin through the intermediates iridodial and iridotrial in the Madagascar periwinkle, Catharanthus roseus, has been best understood [30][31][32][33][34][35]. The pathway in C. roseus is organized in a complex manner, with the enzymes localized in different cell types and subcellular compartments [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Minor peaks do not represent pregnane-like compounds on the basis of a MS data comparison P5ßR activity. Geu-Flores et al (2012) reported that P5ßR activity is expressed in C. roseus during the biosynthesis of a bicyclic monoterpene, namely the iridoid compound nepetalactol (Geu-Flores et al 2012. Subsequently, it has been demonstrated that the precursor substance 8-oxogeranial is converted in a NADPH-dependent manner by a number of recombinant P5ßR enzymes.…”
Section: Enzymatic Datamentioning
confidence: 99%
“…Comparative transcriptomics and metabolomics have been widely and successfully used to elucidate the genes of plant alkaloid metabolism 15, 16, 17, 18. Here we report the use of an available Rauwolfia transcriptome (Medicinal Plant Genomics Resource (MPGR), http://medicinalplantgenomics.msu.edu/index.shtml) to identify and characterize a cytochrome P450 enzyme (CYP82S18) that hydroxylates vinorine to generate vomilenine, which we show exists as rapidly interconverting epimers in solution.…”
mentioning
confidence: 96%